The impact of digital economy on regional green and high-quality economic development in China - Qingjun Li; Zhongxin Kang; Huilin Zheng; Hanxiao Xu; Wenlong Zhu (Technological and Economic Development of Economy)
With the rapid advancement of digitization, the duty of the digital economic climate in advertising regional economic growth is ending up being progressively noticeable. Nonetheless, there is relatively little research study on how the digital economic situation specifically impacts regional environment-friendly and high-quality financial growth (RGED). This study utilizes provincial panel data from 2013 to 2020 in China to empirically assess the effect of the digital economic environment and validates its effect with a fixed impacts model. The study has produced four unique and important findings for: firstly, the effect of the digital economic climate on RGED exhibits nonlinear qualities; Second of all, RGED is significantly influenced by the “∩ - formed” effect of the advancement of the digital economic situation and the degree of industrial digitization; Finally, the influence of digital framework and digital industrialization on RGED exhibits a considerable “U-shaped” pattern; Fourth, the digital economic situation indirectly advertises the growth of RGED by enhancing human funding and updating commercial structure. These conclusions offer beneficial plan support for relevant financial entities to achieve RGED.